Gamified Learning in EFL Classrooms: Students’ Perceptions of Baamboozle Games for Vocabulary Mastery - Fatimah Azzahra; Farida Repelita Waty Kembaren (Universitas Muhammadiyah Mataram, 2025)
Incorporating games into education is an effective strategy to enhance student engagement. This study investigated how EFL students’ emotional reactions and experiences influence their perceptions of the interactivity of Baamboozle games for vocabulary mastery. Conducted at two Integrated Islamic Private Junior High Schools in Medan, the research employed a case study design and a descriptive qualitative methodology, with 8 EFL students participating through observations and semi-structured interviews, which were conducted over a period of four weeks. The thematic analysis revealed that students’ motivation, vocabulary acquisition, and engagement improved significantly, influenced by their emotional responses to the game. These findings highlight the potential of gamified learning platforms like Baamboozle games in enhancing language acquisition and emphasize the role of emotional engagement in mastering vocabulary, which the implication of provides insight for teachers to consider using game-based learning in teaching vocabulary.